Meningkatkan Hasil Belajar IPS Materi Interaksi Manusia Dengan Lingkungan Melalui Media Smart Board Kelas V SDN Punten 1 - Suhartanti, Nur; Irmawati, Leni (IJPSE Indonesian Journal of Primary Science Education, 2023)
The low learning outcomes of human interaction with the environment and its influence on the social, cultural and economic development of Indonesian class V make learning ineffective. The purpose of this research is to improve student learning outcomes. This research was conducted in two cycles with smart board learning media, in early learning the average value was 69, increased by 71 in cycle 1, and cycle II increased by 80. The percentage of completeness in early learning was 29% then in cycle I it increased to 55% and cycle II rose 81%. The percentage of incompleteness before the cycle was 71%, then the first cycle decreased by 45%, and the second cycle decreased again by 19%. The conclusion of the application of smart board learning media (smart board) is able to improve learning outcomes in Social Studies Class V SDN Punten 01 Batu City.